Enter by the Narrow Gate, for Getting New Perspective to Bring Modern Technology Into Order (Journal of Environmental Science Studies, 2023)
One of the main causes of issues about the today’s situation of technology comes from a big mismatch between the new technology based on quantum mechanics (laws in the micro world) and the old perspective (mechanistic viewpoint in the macro world) for more than a half century. I explain this circumstance and show how to settle this problem by solving the so-called measurement problem of quantum mechanics. These give us a new perspective which unify the laws of macro and micro worlds and bring the current technology into order. To go this way would be to enter by the narrow gate.